Computer Aided Policy Making - Wyatt, Ray (Taylor & Francis, 2000)
This book will prove a unique source of information and instruction for anyone seeking to make better human-oriented policy, whether urban planner, business strategist, or manager in the field of education, health or welfare, Ingeniously Wyatt has created two books in one: the main text covers the types of software package available: mainstream software, peripheral software, innovative software, frontier software; the lessons generated from the software are outlined in lesson boxes. Readers can use the text alone to familiarize themselves with the computer packages or read the boxes only, or they can do both.